The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1413-81232011000100021
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar de população adulta residente em área rural da cidade de Ibatiba (ES, Brasil)

Abstract: Consumo alimentar de população adulta residente em área rural da cidade de Ibatiba (ES, Brasil)Consumption to feed of resident adult population in rural area of the city of Ibatiba (ES, Brazil) Resumo Trata- rice, breads, stalk, bean, cow milk, animal fat, margarine, sugar and coffee, and a non habitual consumption of cake, potato, cookies, manioc, sweet potato, chayote, carrot, beet, pumpkin, juice of fruits, banana, orange, guava, mango and tangerine. It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 3 publications
2
16
1
12
Order By: Relevance
“…Regarding the compliance with healthy eating, the ingestion of at least three daily meals and two snacks (step 1) was higher than that observed in a study with adults from the rural zone of Espírito Santo (31.8% vs. 6%), 21 and lower than a study developed with older adults in Sweden. 22 This study showed that splitting meals is inversely proportional to insulin resistance (IR) and metabolic syndrome (MS), despite the traditional risk factors and diet composition.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Regarding the compliance with healthy eating, the ingestion of at least three daily meals and two snacks (step 1) was higher than that observed in a study with adults from the rural zone of Espírito Santo (31.8% vs. 6%), 21 and lower than a study developed with older adults in Sweden. 22 This study showed that splitting meals is inversely proportional to insulin resistance (IR) and metabolic syndrome (MS), despite the traditional risk factors and diet composition.…”
Section: Discussioncontrasting
confidence: 72%
“…The explanation for low ingestion may be due to different factors, for instance: available crops and in between crops characteristic of this food group, as well as the growing of these foods being more directed at commercialization rather than consumption. 21 This step has two categories with grouped analyses. When separated, the ingestion of vegetables increased to a little more than half and the ingestion of fruit to less than a third of the population, agreeing with a study of adults in rural zone of ES.…”
Section: Discussionmentioning
confidence: 99%
“…17 As well as the peculiarities of rural living, the lower QOL of elderly rural dwellers, as cited in several studies, 2,4 may be affected by health-related behavior. Studies suggest that a large section of the rural population suffer from energy deficits, 18,19 eat unhealthy food on a daily basis, including products that are rich in saturated fats and sugars, 20 and do not engage in physical activity for leisure, although they do exercise on a daily basis as they work/ get around. 21 Therefore, health-related behavior, together with the peculiarities of rural life, could play a significant role in the QOL of elderly individuals living in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…No que se refere à alimentação diária habitual, observou-se um elevado consumo de alimentos do grupo A, constatando a característica definidora padrão de alimentação disfuncional, tendo em vista que estes são alimentos que compõem a base da pirâmide alimentar, fontes de carboidratos, que devem ser consumidos em maior quantidade em relação aos demais grupos; entretanto, com equilíbrio, pois induzem o sobrepeso/obesidade por serem altamente energéticos (13) .…”
Section: Discussionunclassified
“…A dieta habitual dos adultos analisados consistia em gorduras animais, açúcar e alimentos refinados, em detrimento ao consumo de frutas, que são fontes ricas de fibras (13) .…”
Section: Discussionunclassified